Comparison between Famous Game Engines and Eminent Games - Mishra, Prerna; Shrawankar, Urmila (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Nowadays game engines are imperative for building 3D applications and games. This is for the reason that the engines appreciably reduce resources for employing obligatory but intricate utilities. This paper elucidates about a game engine, popular games developed by these engines and its foremost elements. It portrays a number of special kinds of contemporary game developed by engines in the way of their aspects, procedure and deliberates their stipulations with comparison.
Keywords: software; gamification; cloud computing; GPGPU; games; IJIMAI